Social Justice Theory and Practice for Social Work - Watts, Lynelle; Hodgson, David (Springer, 2019)
In recent years, social justice has moved to become a central principle and value within social work. As social work educators, we found that many of our conversations with students and our colleagues centred on understanding, explaining and debating different approaches to addressing the many forms of injustice that require attention. We also found this area to be a slippery and difficult terrain to cover with students as it is replete with competing approaches, different conceptions of social justice and different levels of analysis. For example, the view of social justice changes with the level of resolution, depending on whether we are conceptualising justice at the level of individuals or groups and communities. This changes the kinds of questions we can ask about what should be done and why? To address some of these issues, we turned to the literature to try and bring clarity to our discussions about social justice. We figured that others have experienced similar issues in grappling with the complexity of addressing social justice and engaging students in thinking and acting about it. In doing so, we could see there was an opportunity to initiate a dialogue between social work understandings of social justice—built from long engagement with people experiencing poverty, disadvantage, injustice, oppression, stigma and discrimination—and the critical and philosophical literature concerned with developing concepts and principles of social justice. We found that the philosophical literature can offer significant clarity in terms of tracing concepts such as freedom, democracy, theories of distribution and justice, and that critical theories offer a corpus of resources to theorise the way social structures perpetuate oppression, discrimination and stigma. We also found that many of these theoretical ideas have been tested and given significant expression in social work practices. Hence, we have used a mix of influential classic literature, as well as more contemporary sources.
Critical and Philosophical Perspectives